2015
DOI: 10.1186/s40623-015-0200-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-seismic ionospheric response to the 11 April 2012 East Indian Ocean doublet earthquake

Abstract: The 11 April 2012 East Indian Ocean earthquake is unique because of its largest ever recorded aftershock. The main earthquake occurred with a magnitude of 8.6 Mw and was followed by a strong aftershock (8.2 Mw). Our analysis of the main shock indicates that the rupture was a mixture of strike-slip and thrust faults, and significant vertical surface displacements were observed during the event. The prime interest here is to study the post-seismic ionospheric disturbances, along with their characteristics. As bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…The disposition of CIP is normally explained invoking surface displacements either at the epicenter or along the rupture as their source (e.g., Astafyeva & Heki, ; Heki et al, ; Rolland et al, ; Sunil et al, , ). However, the Kaikoura earthquake rupture constitutes contributions from two thrust zones of CCTZ and KCTZ; the total rupture duration of ~100 s (Zhang et al, ) is lower than the characteristic period of acoustic waves (~4 min) in upper atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The disposition of CIP is normally explained invoking surface displacements either at the epicenter or along the rupture as their source (e.g., Astafyeva & Heki, ; Heki et al, ; Rolland et al, ; Sunil et al, , ). However, the Kaikoura earthquake rupture constitutes contributions from two thrust zones of CCTZ and KCTZ; the total rupture duration of ~100 s (Zhang et al, ) is lower than the characteristic period of acoustic waves (~4 min) in upper atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Reddy and Seemala, 2015;Sunil et al, 2015;Cahyadi and Heki, 2015;Chum et al, 2012;Rolland et al, 2011a,b;Tsugawa et al, 2011;Galvan et al, 2011;Saito et al, 2011;Heki, 2011;). These ionospheric perturbations carry traceable information about the earthquake itself that generated them.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to the magnitude of the earthquake and focal depth, there is some evidence that the earthquake focal mechanism , atmospheric acoustic resonance conditions (e.g. at 3.7 and 4.4 mH z , Nishida et al, 2000;Rolland et al, 2013;Sunil et al, 2015;Tahira, 1995), directivity and apparent velocity (Heki and Ping, 2005), geomagnetic latitude, and other factors, can influence the intensity of ionospheric responses. While some of these aspects are addressed by Cahyadi and Heki (2015) using 21 earthquakes between M w 6.6 and 9.2, TEC response amplitudes during quiet and disturbed geomagnetic conditions have been compiled by Perevalova et al (2014), which can serve as ready reference to seismo-ionospheric studies.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…But for Moderate earthquakes of magnitudes Mw from 5 to 5.9, the perturbations tend to become small (Ducic et al, 2003). It has been shown in the previous studies that dense GPS arrays can provide an opportunity to investigate ionospheric perturbations in the most efficient manner (Reddy, 2016;Reddy and Seemala, 2015;Seemala and Valladares, 2011;Ogawa et al, 2012;Sunil et al, 2015;Heki, 2013, 2015). Some advanced techniques, such as HF Doppler sounding (Artru et al, 2004;Ogawa et al, 2012), DEMETER (Ryu et al, 2014), Over-The-Horizon Radar (Occhipinti et al, 2010), Faraday rotation measurements using linearly polarized electromagnetic signals from geostationary satellites (Davies, 1980), and GPS (Ducic et al, 2003;Heki, 2011;Saito et al, 2011) have also shown that ionospheric plasma perturbations can be generated by large earthquakes.…”
Section: Introductionmentioning
confidence: 96%